Gaston Eysselinck and his Masterpiece. The Post Office Building in Ostend (1945-1953) - Dubois, Marc (Docomomo Journal, 2012)
The city of Ostend became severely damaged during World War II. Practically all the main public buildings were destroyed: the City Hall, the Casino, the Horse Race–Track, the main Post Office building, etc. The city decided to rebuild a new Post Office on the location of the first construction. In 1945, architect Gaston Eysselinck (1907–1953) from Ghent was assigned to design the new main Post Office (PTT), including the telephone and telegraph offices (RTT) and the technical infrastructure. The project in Ostend was his first big assignment.